Performance Measures of Swarm based Active Network for Multiclass Packet Routing-A Simulation study - Mavromoustakis, Constandinos X.; Karatza, Helen D. (My University, 2005)
Pervasive computing environments demand reliability and multiclass QoS for end to end real time applications. The concept of active network has been recently adopted in many distributed environments. This paper describes and examines the combination of the active network concept with swarm based control method called Swarm-based Active Network scheme for optimized and tunable QoS priority routing. This hybrid scenario is using the bandwidth clustering approach in which packets are following the predetermined path allocated by swarm based packets (embedded swarms). This mechanism enables the adaptation of the system to new conditions, and does not require message bro-kers to fulfill multiclass QoS demands. Simulation results reveal the response in terms of the end-to-end delay, available bandwidth and packet loss of this scheme under different traffic measures.
Keywords: Bandwidth Clustering; Embedded Packet based Swarms; Tunable Scheduling Scheme